Effectiveness of Education Based on the Health Belief Model on Performing Preventive Measures for Breast Cancer Among Female Teachers in Zahedan - Khadijeh Kalan-Farmanfarma; Iraj Zareban; Zahra Jalili; Mahnaz ShahrakiPour (Hamadan University of Medical Sciences, 2014)
Introduction: Preventive behaviors such as screening tests have an important role in prevention and control of breast cancer. Therefore, this study aimed to determine the effect of educational programs on preventive behaviors of breast cancer based on the health belief model among female teachers of guidance schools in Zahedan city. Materials and Methods: This quasi-experimental study was performed on 240 female teachers from (120 participants in each of the control and intervention groups) Zahedan guidance schools. The data-gathering tool was a multipart questionnaire containing demographic variables, knowledge and health belief model structures. An educational program was performed based on the health belief model in five sessions through lectures, training videos, question and answer session for participants in the intervention group. Questionnaires were filled before and two months after the intervention in the two groups. Data was analyzed by independent T-test, chi-square and multiple linear regressions using SPSS-15 software. Results: There was no meaningful difference in the mean scores of knowledge, health belief model constructs, and performance between the two groups before the educational intervention, but the mean scores of variables increased significantly after the intervention (P< 0.05). Conclusion: The health belief model was effective to promote preventive behaviors. Hence, educational interventions with an emphasis on raising awareness, change in beliefs and improving self-efficacy regarding breast cancer are recommended